Characteristics of Inceptisols derived from basaltic andesite from several locations in volcanic landform - Rufaidah Qonita Muslim; Pronika Kricella; Mira Media Pratamaningsih; Setiyo Purwanto; Erna Suryani; Sofyan Ritung (Universitas Sebelas Maret, 2020)
The widespread of Inceptisols in Indonesia especially in volcanic landform has the characteristics potentially to be used as agricultural land. This study aimed to identify the characteristics of Inceptisols found in volcanic landform developed from basaltic andesite parent materials. Soil samples were collected in 6 locations. A total of 23 samples were taken from each horizon from 6 pedons for physical, chemical, and mineral analysis. The results showed that Inceptisols had different colors depending on land use and mineral content, but were dominated by yellowish brown to dark brown with hue 7.5YR to 10YR, color value varied from 2.5 to 4, and croma varied from 1 to 6. Base saturation varied from low to very high, cation exchange capacity varied from low to high. Soil textures were dominated by clay, clay loam, and sandy loam. Three pedons in Purwakarta, Bandung Barat, and Jember Regency, Java Island were dominated by weatherable minerals, while the others obtained in Seluma, Rejang Lebong, and Ogan Komering Ulu Selatan Regency, Sumatera Island were dominated by resistant minerals such as opaque and quartz. Physical, chemical, and mineral content can be used as a reference in soil management and recommendation for balanced fertilization.